BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN MINAT IBU MENGGUNAKAN ALAT KONTRASEPSI IUD - Sukmawati Anwar; Grenny Zovianny Rahakbauw; Susanti Pratamaningtyas; Eny Sendra (Ensiklopedia of Journal, 2026)
Abstract: Population issues have long been a global concern, both in developed and developing countries, including Indonesia. A large population does not always benefit a country if it is not balanced with adequate human resources. The purpose of this study was to identify several factors related to mothers' interest in using IUD contraceptives. A cross-sectional study design was used in this study. The research was conducted in the working area of the Sungai Bulian Community Health Center. The research was conducted in April 2025. The research population consisted of active family planning acceptors in the working area of the Sungai Bulian Community Health Center. The sample consisted of 65 respondents. The sampling technique used was purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between mothers' knowledge (p value: 0.000) and husbands' support (p value: 0.000) with mothers' interest in using IUD contraception. It is recommended that health centers improve public understanding by engaging with the community. It is necessary to change the knowledge and socio-cultural beliefs of the community regarding misconceptions about IUDs, especially for women of childbearing age, by providing counseling and education explaining what IUD contraceptives are, how they are inserted, their effectiveness, advantages, and disadvantages.Keywords: Spousal Support, IUD, Maternal Knowledge.